STUDENTS' SPEAKING DIFFICULTIES IN ESP: ENGLISH FOR ACCOUNTING - Prasongko, Angga (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This study aims to find problems that influenced the student’s speaking difficulties in English Specific Purposes especially in the accounting field. The results are necessary to find some solutions so it can graduate qualified students who are ready for facing some futures career challenge. Nowadays interpersonal communications skill is required for employees. This research conducted in the accounting study program and the students as key informants. This study uses a descriptive qualitative approach. According to the findings, internal and external factors both have an influence on students’ speaking difficult. The recommendations from this research are by creating good emotional relationships between teacher and students, conducting students cantered learning, and fun cooperative learning.